EFFECTIVENESS OF FUMIGAN ORANGE PEEL EXTRACT (CITRUS NOBILIS) AS A BOTANICAL PESTICIDES IN CULEX SP. - Nassaf, Jauharati; Safrida, Safrida; Syafrianti, Devi; Hasanuddin, Hasanuddin; Andayani, Dewi (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2020)
ABSTRACTBotanical pesticides are natural-made pesticides that come from plants. Siam orange peel waste (Citrus nobilis) can be used as the main ingredient of botanical pesticides because it contains bioactive compounds. The purpose of this study was to determine affect the concentration of siam citrus fruit peel extracts to the mortality of Culex sp. Mosquitoes, and to find out the time interval of exposure of siam citrus peel extract that affects the Culex sp. Mosquitoes. This type of research is experimental with a quantitative approach. The experimental design used was a Factorial Complete Randomized Design consisting of seven different treatments and three observation times. These treatments are the concentration of siam citrus fruit extract 0% as a negative control, 30%, 45%, 60%, 75%, 90%, and commercial products as a positive control with three time observations, treatment four replications were performed. Data were analyzed using Variant Analysis and conducted further tests in the form of Honest Real Difference (BNJ). The results showed the lowest average percentage of mosquito deaths was at a concentration of 30% with an observation time of 20 minutes which was 5% while the highest mosquito mortality was at a concentration of 90% with a time of 60 minutes observation of 100%. The conclusion from this research proves that there is an effect of extracts of rind on the death of Culex mosquitoes and there is an influence of the time interval of extract exposure to Culex mosquito mortality with an optimal time for 60 minutes. Keywords: Botanical Pesticides, Siam Orange, Culex sp.ABSTRAKPestisida nabati merupakan pestisida berbahan alami yang berasal dari tumbuh-tumbuhan. Limbah kulit buah jeruk siam (Citrus nobilis) dapat dijadikan sebagai bahan utama pestisida nabati karena mengandung senyawa bioaktif. Tujuan riset ini adalah mengetahui pengaruh konsentrasi ekstrak kulit buah jeruk siam pada mortalitas nyamuk Culex sp, dan untuk mengetahui jarak waktu pemaparan ekstrak kulit buah jeruk siam yang berpengaruh pada nyamuk Culex sp. Jenis riset ini adalah eksperimental dan pendekatan kuantitatif. Rancangan percobaan yang digunakan Rancangan Acak Lengkap Faktorial terdiri dari tujuh perlakuan yang berbeda dan tiga waktu pengamatan. Perlakuan tersebut adalah konsentrasi ekstrak kulit buah jeruk siam 0% sebagai kontrol negatif, 30%, 45%, 60%, 75%, 90%, dan produk komersil sebagai kontrol positif dengan tiga waktu pengamatan, perlakuan dilakukan sebanyak empat ulangan. Data dianalisis menggunakan Analisis Varian, kemudian uji lanjut berupa Beda Nyata Jujur (BNJ). Hasil riset menunjukkan persentase rata-rata kematian nyamuk terendah adalah pada konsentrasi 30% dengan waktu pengamatan 20 menit yaitu sebesar 5% sementara kematian nyamuk tertinggi adalah pada konsentrasi 90% dengan waktu pengamatan 60 menit yaitu sebesar 100%. Simpulan dari riset ini membuktikan bahwa terdapat pengaruh ektrak kulit buah jeruk siam pada kematian nyamuk Culex dan terdapat pengaruh jarak waktu pemaparan ekstrak terhadap kematian nyamuk Culex dengan waktu optimal selama 60 menit. Kata Kunci: Pestisida Nabati, Jeruk Siam, Culex sp.